ISSUES OF DEVELOPMENT OF LEGAL SERVICES IN UZBEKISTAN - Rakhmatov Saidumar Shukhrat ogli (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: The development of legal services plays a crucial role in ensuring the rule of law, protecting human rights, and improving the effectiveness of public administration. In Uzbekistan, large-scale legal reforms have been implemented in recent years to modernize the legal system, expand access to legal services, and increase public trust in legal institutions. However, despite significant progress, a number of systemic and practical issues continue to hinder the full development of legal services. This article analyzes the current state of legal services in Uzbekistan, identifies key challenges, and proposes possible solutions for their improvement.